Effectiveness of Non-Tax State Revenue Management through SIMPONI: A Case Study at the Harbormaster's Office and the Lake Toba Port Ferry Authority - Said Dariadi Ramadhan; Nursantri Yanti; Laylan Syafina (Jurnal Investasi Islam, 2026)
Non-Tax State Revenue (PNBP) plays a vital role in supporting national finances, yet studies examining implementation gaps in PNBP accounting systems at inland ports remain limited, particularly regarding the lack of integration between operational logbooks and digital financial systems. This study analyzes the effectiveness of PNBP management at the Lake Toba Harbormaster and Ferry Authority Office (KSOP), with a specific focus on the integration gap between manual ship logbooks and the SIMPONI digital platform. Using a socio-technical systems perspective, the research highlights how partial digitalization can create administrative inefficiencies and reduce the quality of financial information. A descriptive qualitative case study approach was employed. Data were collected through purposive sampling involving the Head of KSOP, the Head of the Administration Subdivision, and financial staff. Data validity was ensured through source triangulation, while analysis followed thematic coding procedures consisting of data reduction, data display, and conclusion drawing. The findings indicate that although PNBP collection procedures comply with existing regulations, management effectiveness remains suboptimal due to non-integrated manual logbook records, system output errors, and limited staff competencies. These issues contribute to reporting delays and increase the risk of inaccurate financial information. The study contributes to public sector accounting literature by demonstrating that effective PNBP management depends not only on regulatory compliance and the availability of digital systems but also on comprehensive system integration and institutional capacity. Practical recommendations include integrating ship logbooks with SIMPONI, providing continuous technical training, and strengthening internal verification mechanisms to enhance transparency, accountability, and the overall effectiveness of PNBP management.